INDIGENOUS KNOWLEDGE ON LAND EVALUATION AND SOIL FERTILITY MANAGEMENT AMONG RURAL FARMERS IN MUBI NORTH LOCAL GOVERNMENT AREA, ADAMAWA STATE, NIGERIA - Danjuma Ijudigal Garandi; Hassan, Saad Tanko; Hyelnacha, A. Bukar; Abbas, Bashir; Mohammed, Saadu Dasin; Paulinus, I. Chukwu; Peter, Gabul; Phelimon, Wesley (FUDMA Journal of Sciences, 2025)
The study was carried out to analysed the indigenous knowledge system on land evaluation and  soil fertility management among rural farmers in selected communities in Mubi North. Understanding farmers' indigenous knowledge on land evaluation and soil fertility management practices means understanding local realities that are important for sustainable agricultural productivity. This study was conducted in three rural communities in Mubi North to evaluate the perception of rural farmers on traditional land evaluation and soil fertility management practices through direct and indirect interviews. Structured questionnaires were administered to 100 rural farmers in three farm settlements. The major local methods of evaluation adopted by majority of the farmers include the vigour of native vegetation, presence of certain indicator plants and visual appraisal. Fertility ranking of the farmers correlated with values of Organic carbon (r = 603* p < 0.05) and Available P. (r = 647* p < 0.05) obtained from laboratory analysis. Though a large proportion of farmers (72 %) have applied chemical fertilizers (mainly to arable crops) at one time or the other, cultural methods such as multiple cropping (intercropping) and cover cropping are employed to manage soil fertility in their farms. Rural farmers demonstrated significant knowledge of their soils and the environment acquired by experiences that have been tested by many years of living close to the farmland. In view of the importance in applying a holistic approach to study land evaluation, local soil knowledge provides key linkages between ancient and modern soil management.
Keywords: Indigenous knowledge; land evaluation; rural farmers; soil fertility